512 Patient and physical therapist experiences with integrating an eHealth pain self-management program into clinical care. (April 2022) - Coronado, Rogelio; Block, Shannon; Gonzalez, Katelyn; Rhoten, Bethany; Brintz, Carrie; McKernan, Lindsey; Kirkhart, Tricia; Wegener, Stephen; Archer, Kristin
Abstract : OBJECTIVES/GOALS: eHealth programs centered on cognitive behavior therapy (CBT) can be supported by physical therapists to feasibly deliver psychologically-informed physical therapy (PIPT). This study assessed patient and physical therapist (PT) perspectives of adding a CBT-based eHealth program to physical therapy. METHODS/STUDY POPULATION: In our uncontrolled pilot study, PTs were trained in motivational interviewing (MI) to support patient engagement with a 7-module eHealth CBT-based pain self-management program that accompanied a course of PT. Interviews were conducted with a convenience sample of 13 patients with chronic back and/or neck pain and 9 PTs to evaluate experiences with the eHealth program, perceived benefits, barriers and facilitators to integration, and future recommendations for implementation from both perspectives. Interview data were recorded, transcribed, and analyzed using qualitative content analysis for core themes. RESULTS/ANTICIPATED RESULTS: Patients benefited from the eHealth program, especially relaxation (69% of respondents) and meditation/mindfulness (62%). Time and technology were barriers for eHealth engagement (23% and 15%). Most (92%) patients reported their therapist reviewed eHealth progress, although one-third of patients wanted more discussion and feedback on eHealth content. PTs felt the eHealth program was valuable (67%), user-friendly (56%), and took minimal effort to support (78%). Some (44%) therapists felt more confident after MI training to support patient engagement. PTs recommended offering patients tablets (i.e., iPads) for clinic or home use and additional therapist training in MI. DISCUSSION/SIGNIFICANCE: PTs and patients valued a clinician-supported eHealth program, suggesting an acceptable option for PIPT. Future implementation work aims to identify optimal therapist training in MI and additional strategies to overcome time or technology barriers.